Modified nano silicon dioxide, preparation method and application thereof, resin composition and cured epoxy resin

Through the bonding reaction between modified nano silica and epoxy resin, the problem of insufficient curing performance and mechanical strength of epoxy resin materials is solved, and the effects of high hardness and wear resistance are achieved, while maintaining the fluidity of the material .

CN119264381AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311776244.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-01-07
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

The existing epoxy resin materials have shortcomings in curing performance and mechanical strength, especially when it is necessary to maintain transparency and high hardness or wear resistance, the addition of powder fillers will affect the flowability, and the performance improvement of traditional modification methods is limited.

Method used

Modified nano silica is adopted, which has a small particle size, a large specific surface area and a high amino content. By bonding with the epoxy groups in the epoxy resin, the compressive strength and glass transition temperature after curing are improved. . The modified nanosilica exhibits a dendritic morphology on the surface of nanosilica particles by a specific preparation method, enhancing its crosslinking properties with epoxy resin.

Benefits of technology

The compressive strength and glass transition temperature of the cured epoxy resin are significantly improved, making it less likely to deform at high temperatures, meeting the needs of high hardness and wear resistance, while maintaining good fluidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264381A_ABST
    Figure CN119264381A_ABST
Patent Text Reader

Abstract

The invention relates to the field of organic polymers, and discloses modified nano silicon dioxide and a preparation method and application thereof, a resin composition and cured epoxy resin, the modified nano silicon dioxide has a structure as shown in a formula (1): # imgabs0 #, M is nano silicon dioxide particles, x is an integer of 1-4, and R is alkyl with the carbon atom number of 1-4; n is an integer of 0-3, m is an integer of 1-3, and n + m = 3; a is a structural unit from an anhydride compound, and B is a structural unit from a polyamino compound. The amino content of the modified nano silicon dioxide is high, the modified nano silicon dioxide can be subjected to bonding reaction with epoxy groups in epoxy resin when being added into the epoxy resin, and the advantages of the modified nano silicon dioxide and the epoxy groups are fully played, so that the cured epoxy resin has higher compressive strength, the glass-transition temperature of the epoxy resin can be increased, and the epoxy resin is not easy to deform at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic polymers, and in particular to modified nano silicon dioxide and a preparation method and application thereof, a resin composition and a cured epoxy resin. Background Art

[0002] As a traditional polymer material, epoxy resin is used in many subdivided material fields, such as coatings, adhesives, etc. Most pure epoxy resins are liquid or viscous substances. When used as polymer functional materials, they must be combined with curing agents to work. Curing agents contain a large number of active groups, which can react chemically with the active sites in the resin and obtain the final solid material through cross-linking and curing. In actual industrial formulas, pigments, fillers, functional additives, etc. are also added to the resin. For example, a large amount of powder fillers are added to increase the hardness of the material and reduce costs. However, not all materials can be hardened by adding cheap powders. For example, the varnish that is most easily damaged in anti-corrosion coatings needs to maintain transparency and high hardness. For example, the topcoat in floor coatings needs strong wear resistance and good fluidity, and too much powder cannot be added. In response to these problems, the traditional solution is to continuously modify the resin and organic curing agent. This method has achieved certain results, but due to the inherent defects of organic polymer materials themselves, the performance improvement is limited. Therefore, it is necessary to find another way to break through the inherent defects of organic polymer materials and improve the performance of the materials from the essence. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems of poor curing performance and mechanical strength and high cost in the prior art, and to provide a modified nano-silicon dioxide, a preparation method thereof and an application thereof. The modified nano-silicon dioxide has a smaller particle size and a larger specific surface area, and has good dispersibility in epoxy resin. The modified nano-silicon dioxide has a high amino content, and the amino groups present a dendritic morphology on the surface of the nano-silicon dioxide particles. When the modified nano-silicon dioxide is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of the two, so that the cured epoxy resin has a larger compressive strength, and at the same time can increase its glass transition temperature, so that it is not easy to deform at high temperatures.

[0004] In order to achieve the above object, the first aspect of the present invention provides a modified nano-silicon dioxide, characterized in that the modified nano-silicon dioxide has a structure shown in formula (1):

[0005]

[0006] Wherein, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;

[0007] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;

[0008] A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.

[0009] The second aspect of the present invention provides a method for preparing modified nano-silicon dioxide, characterized in that the method comprises the following steps:

[0010] S1. In the presence of a protective gas, dispersing nano-silica particles M in a first solvent, adding aminosilane to carry out a first reaction, and obtaining amino-functionalized nano-silica as shown in formula (3);

[0011]

[0012] S2, in the presence of a second solvent, subjecting the amino-functionalized nano-silica to a second reaction with an acid anhydride compound to obtain a carboxyl-functionalized nano-silica represented by formula (4);

[0013]

[0014] S3. In the presence of an alkaline catalyst, the carboxyl-functionalized nano-silica is mixed with a condensation agent, activated, and then a polyamino compound is added to carry out a third reaction to obtain modified nano-silica.

[0015] The third aspect of the present invention provides a modified nano-silicon dioxide prepared by the above method.

[0016] A fourth aspect of the present invention provides a use of the modified nano-silica as a curing agent in epoxy resin.

[0017] A fifth aspect of the present invention provides an epoxy resin composition, characterized in that the epoxy resin composition comprises a curing agent component and a resin component;

[0018] The curing agent component contains the modified nano-silicon dioxide described in the first aspect or the third aspect;

[0019] The resin component includes epoxy resin.

[0020] Wherein, the curing agent component and the resin component exist independently of each other.

[0021] In the present invention, based on 100 parts by weight of epoxy resin, the content of the modified nano-silicon dioxide is 20-80 parts by weight.

[0022] In the present invention, the epoxy resin composition may further contain emulsifiers, enhancers, etc. commonly used in the art. There is no particular limitation on the type and amount of the emulsifiers and enhancers, which may be conventional types and amounts in the art.

[0023] The sixth aspect of the present invention provides a cured epoxy resin, characterized in that the cured epoxy resin is prepared from the epoxy resin composition described in the fifth aspect of the present invention.

[0024] Through the above technical scheme, the modified nano-silica and its preparation method and application, resin composition and cured epoxy resin provided by the present invention obtain the following beneficial effects: the modified nano-silica has a smaller particle size and a larger specific surface area, has good dispersibility in epoxy resin, and has a high amino content, and presents a dendritic morphology on the surface of the nano-silica particle M. When it is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of the two, so that the cured epoxy resin has a larger compressive strength, and at the same time can increase its glass transition temperature, so that it is not easy to deform at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a real photo of modified nano-silicon dioxide with an average particle size of 30 nm dispersed in water in Preparation Example 1;

[0026] Figure 2 This is a TEM characterization image of modified nano-silica with an average particle size of 30 nm in Preparation Example 1;

[0027] Figure 3 This is a SEM characterization image of modified nano-silica with an average particle size of 30 nm in Preparation Example 1;

[0028] Figure 4 This is a real photo of the modified nano-silicon dioxide with an average particle size of 200 nm dispersed in water in Preparation Example 2;

[0029] Figure 5 This is a TEM characterization image of the modified nano-silica with an average particle size of 200 nm in Preparation Example 2;

[0030] Figure 6 This is the SEM characterization picture of the modified nano-silica with an average particle size of 200 nm in Preparation Example 2. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] The first aspect of the present invention provides a modified nano-silicon dioxide, characterized in that the modified nano-silicon dioxide has a structure shown in formula (1):

[0033]

[0034] Wherein, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;

[0035] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;

[0036] A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.

[0037] In the present invention, the nano-silica particles M are modified with polyamino groups on the basis of carboxyl modification, so that a dendritic morphology is presented on the surface of the nano-silica particles M. When the nano-silica particles M are added to the epoxy resin, a bonding reaction can occur with the epoxy groups in the epoxy resin, and the advantages of the two are fully utilized, so that the cured epoxy resin has a greater compressive strength, and at the same time, its glass transition temperature can be increased, so that it is not easy to deform at high temperatures.

[0038] According to the present invention, the acid anhydride compound is at least one selected from maleic anhydride, phthalic anhydride and succinic anhydride.

[0039] According to the present invention, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000 having a structure shown in formula (2):

[0040]

[0041] Here, p is an integer from 1 to 6.

[0042] Furthermore, the molecular weight of the nonlinear polyethyleneimine is 1500-2500.

[0043] In the present invention, the polyamino compound is selected from the above compounds, so that the amino content in the modified nano-silicon dioxide is high, and the curing performance of epoxy resin is further improved.

[0044] In the present invention, the poly(ethylene) polyamino compound may be triethylenediamine, triethylenetetramine, pentaethylenehexamine or hexaethyleneheptamine.

[0045] According to the present invention, the particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g.

[0046] Furthermore, the particle size of the nano-silicon dioxide particles M is 30-200 nm, and the specific surface area is 50-200 m 2 / g.

[0047] According to the present invention, the particle size of the modified nano-silicon dioxide is 10-500nm, and the specific surface area is 50-500m 2 / g.

[0048] In the present invention, when the particle size and specific surface area of ​​the modified nano-silicon dioxide meet the above ranges, the smaller the particle size, the better the dispersibility in the epoxy resin, thereby improving the curing performance of the epoxy resin.

[0049] Furthermore, the particle size of the modified nano-silicon dioxide is 30-500nm, and the specific surface area is 50-300m 2 / g.

[0050] According to the present invention, the amino content of the modified nano-silicon dioxide is 0.1-5 mmol / g.

[0051] In the present invention, when the amino content of the modified nano-silica satisfies the above range, a dendritic morphology can be presented on the surface of the nanoparticles, thereby increasing the cross-linking speed and cross-linking density of the epoxy resin containing the modified nano-silica.

[0052] Furthermore, the amino content of the modified nano-silica is 0.5-5 mmol / g.

[0053] The second aspect of the present invention provides a method for preparing modified nano-silicon dioxide, characterized in that the method comprises the following steps:

[0054] S1. In the presence of a protective gas, dispersing nano-silica particles M in a first solvent, adding aminosilane to carry out a first reaction, and obtaining amino-functionalized nano-silica as shown in formula (3);

[0055]

[0056] S2, in the presence of a second solvent, subjecting the amino-functionalized nano-silica to a second reaction with an acid anhydride compound to obtain a carboxyl-functionalized nano-silica represented by formula (4);

[0057]

[0058] S3. In the presence of an alkaline catalyst, the carboxyl-functionalized nano-silica is mixed with a condensation agent, activated, and then a polyamino compound is added to carry out a third reaction to obtain modified nano-silica.

[0059] In the present invention, the method is simple to operate, the raw materials are easily available, the yield is high, and the product modified nano silicon dioxide is solid, non-flammable and non-explosive, and has good storage and transportation safety.

[0060] In the present invention, the protective gas is nitrogen and / or an inert gas.

[0061] In the present invention, steps S1, S2 and S3 each independently comprise separation, washing and drying steps.

[0062] Furthermore, there is no particular limitation on the separation method, and for example, it may be at least one of filtration, rotary evaporation or centrifugal separation.

[0063] Furthermore, there is no particular limitation on the washing conditions. For example, the washing can be performed 3-4 times using conventional solvents in the art, wherein the solvent can be at least one of methanol, ethanol, and acetone. Preferably, in step S1, acetone and dichloromethane are used for washing.

[0064] In the present invention, in step S1, acetone and dichloromethane are preferably used for washing, so that unreacted aminosilane can be better washed and removed, thereby improving the purity of the product.

[0065] According to the present invention, in step S1, the mass ratio of the nano-silica particles M to the aminosilane is 5-100:1.

[0066] In the present invention, when the mass ratio of the nano-silica particles M to the aminosilane satisfies the above range, the amino content is more appropriate, and the cross-linking speed and cross-linking density of the epoxy resin containing the modified nano-silica are further improved.

[0067] Furthermore, the mass ratio of the nano-silica particles M to the aminosilane is 10-50:1.

[0068] According to the present invention, the aminosilane is at least one selected from aminopropyltriethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane and aminopropylmethyldiethoxysilane.

[0069] According to the present invention, the conditions of the first reaction include: reaction temperature of 120-160° C., and reaction time of 2-24 h.

[0070] Furthermore, the conditions of the first reaction include: reaction temperature of 120-140° C., and reaction time of 8-16 h.

[0071] According to the present invention, in step S2, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 5-100:1.

[0072] Furthermore, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 10-50:1.

[0073] According to the present invention, the acid anhydride compound is at least one selected from maleic anhydride, phthalic anhydride and succinic anhydride.

[0074] According to the present invention, the conditions of the second reaction include: reaction temperature of 90-160° C., and reaction time of 2-12 h.

[0075] Furthermore, the conditions of the second reaction include: reaction temperature of 90-120° C., and reaction time of 6-12 h.

[0076] According to the present invention, the first solvent and the second solvent are each independently selected from at least one of toluene, xylene, benzene and N,N-dimethylformamide.

[0077] According to the present invention, in step S3, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1:0.05-0.5:0.01-0.1:0.1-5.

[0078] In the present invention, when the mass ratio of the carboxyl-functionalized nano-silica, the condensing agent, the alkaline catalyst and the polyamino compound meets the above preferred range, the obtained modified nano-silica has the best comprehensive performance and further improves the curing performance of epoxy resin.

[0079] Furthermore, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1:0.05-0.3:0.01-0.05:0.1-4.

[0080] According to the present invention, the condensing agent is selected from one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.

[0081] According to the present invention, the base catalyst is selected from at least one of 4-dimethylaminopyridine, 1,8-diazabicycloundec-7-ene and triethylamine.

[0082] According to the present invention, the conditions of the third reaction include: reaction temperature of 0-40° C., and reaction time of 2-48 h.

[0083] Furthermore, the conditions of the third reaction include: reaction temperature of 10-25°C, reaction time of 8-16h.

[0084] According to the present invention, in step S3, the activation conditions include: activation temperature of 10-25° C., and activation time of 8-24 h.

[0085] According to a particularly preferred embodiment of the present invention, specifically, the modified nano-silicon dioxide is prepared according to the following steps, wherein x is 3, m is 3, and n is 0:

[0086] 1. Preparation of amino-functionalized nano-silica:

[0087]

[0088] 2. Preparation of carboxyl functionalized nano-silica:

[0089]

[0090] 3. Preparation of modified nano-silica:

[0091]

[0092] The third aspect of the present invention provides a modified nano-silicon dioxide prepared by the above method.

[0093] A fourth aspect of the present invention provides a use of the modified nano-silica as a curing agent in epoxy resin.

[0094] In the present invention, the modified nano-silica has a small particle size, and the force formed by combining with the epoxy groups in the epoxy resin is much greater than the van der Waals force, thereby forming a more perfect interface, thereby inducing more microcracks, consuming and absorbing more energy, and at the same time, when the cracks expand in the resin system, they encounter the obstruction and passivation effect of the modified nano-silica, thereby enhancing the epoxy resin system.

[0095] Furthermore, the modified nano-silica has a small particle size and good dispersibility in epoxy resin, and can migrate well to the surface of epoxy resin during the curing process, thereby increasing the roughness of the surface of the cured epoxy resin, so that the epoxy resin can be firmly attached to the surface of the substrate.

[0096] Furthermore, the active groups on the surface of the modified nano-silica, such as hydroxyl groups or carboxyl groups, can undergo a bonding reaction with epoxy groups in the epoxy resin, thereby improving the mechanical strength of the epoxy resin after curing.

[0097] A fifth aspect of the present invention provides an epoxy resin composition, characterized in that the epoxy resin composition comprises a curing agent component and a resin component;

[0098] The curing agent component contains the modified nano-silicon dioxide described in the first aspect or the third aspect;

[0099] The resin component includes epoxy resin.

[0100] Wherein, the curing agent component and the resin component exist independently of each other.

[0101] In the present invention, based on 100 parts by weight of epoxy resin, the content of the modified nano-silicon dioxide is 20-80 parts by weight.

[0102] In the present invention, the epoxy resin composition may further contain emulsifiers, enhancers, etc. commonly used in the art. There is no particular limitation on the type and amount of the emulsifiers and enhancers, which may be conventional types and amounts in the art.

[0103] The sixth aspect of the present invention provides a cured epoxy resin, characterized in that the cured epoxy resin is prepared from the epoxy resin composition described in the fifth aspect of the present invention.

[0104] In the present invention, the compressive strength of the cured epoxy resin is not less than 28 MPa, and the glass transition temperature is not less than 120°C.

[0105] The present invention will be described in detail below by way of examples. In the following examples,

[0106] The morphological parameters of modified nano-silica were measured by transmission electron microscopy (TEM) and scanning electron microscopy (SEM);

[0107] The dispersion index (PDI) of modified nano-silica was measured by laser particle size analyzer (DLS);

[0108] The amino content in modified nano-silica was obtained by acid-base titration test;

[0109] Nano-silica particles M were purchased from MacLean’s reagent;

[0110] Aminopropyltriethoxysilane was purchased from MacLean's reagent;

[0111] Maleic anhydride, purchased from MacLean's reagent;

[0112] Dicyclohexylcarbodiimide (DCC) was purchased from MacLean's reagent;

[0113] Diisopropylcarbodiimide (DIC) was purchased from MacLean's reagent;

[0114] 1,8-diazabicycloundec-7-ene (DBU) was purchased from MacLean's reagent;

[0115] 4-Dimethylaminopyridine (DMAP) was purchased from MacLean's reagent;

[0116] Tetraethylenepentamine, purchased from MacLean's reagent;

[0117] Polyethyleneimine, molecular weight 1500, purchased from MacLean's reagent;

[0118] Other reagents were purchased from commercial sources.

[0119] Example 1

[0120] S1. Preparation of aminopropyl functionalized nano-silica:

[0121] Weigh 2g of the average particle size of 30nm and the specific surface area of ​​200m 2 / g of nano-silica particles M were dispersed in 100mL of anhydrous toluene, and then 0.2g of aminopropyltriethoxysilane was added. The mixture was refluxed and stirred at 150°C for 24 hours under nitrogen protection. After the reaction, the solid product was centrifuged to obtain the solid product. The solid product was repeatedly washed with acetone and dichloromethane for 3 times, and vacuum dried at 40°C for 12 hours to obtain aminopropyl-functionalized nano-silica.

[0122] S2. Preparation of carboxyl functionalized nano-silica:

[0123] Weigh 2 g of the aminopropyl-functionalized nano-silica prepared above, disperse it in 50 mL of xylene, add 0.2 g of maleic anhydride, reflux and stir at 160 ° C for 6 hours under nitrogen protection, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40 ° C for 12 hours to obtain carboxyl-functionalized nano-silica.

[0124] S3. Preparation of modified nano-silica:

[0125] Weigh 1 g of the prepared carboxyl functionalized nano-silica, disperse it in 50 mL of toluene, add 0.25 g of diisopropylcarbodiimide (DIC) and 0.06 g of 1,8-diazabicycloundec-7-ene (DBU), activate it at room temperature (25°C) for 1 hour, then add 4 g of polyethyleneimine (number average molecular weight of 1500), continue to react at room temperature for 12 hours, wash it repeatedly with methanol for 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain modified nano-silica A1 with the structure of formula (1), wherein n is 0, m is 3, and x is 3.

[0126] The particle size of the modified nano-silicon dioxide A1 is 30 nm and the specific surface area is 300 m 2 / g, and the amino content is 2mmol / g.

[0127] like Figure 1 As shown, the prepared modified nano-silica A1 is dispersed more evenly in water and has good dispersibility; Figure 2 and Figure 3 They are transmission electron microscope TEM and scanning electron microscope SEM images of high-density amino-modified nano-silica. Figure 2-3 It can be seen that the high-density amino-modified nano-silica particles are relatively uniform. The modified nano-silica A1 was tested using a laser particle size analyzer, and its dispersion coefficient PDI was 0.11.

[0128] Example 2

[0129] S1. Preparation of aminopropyl functionalized nano-silica:

[0130] 5g of average particle size is 200nm and specific surface area is 50m 2 / g of nano-silica particles M were dispersed in 100mL of anhydrous toluene, and then 0.5g of aminopropyltriethoxysilane was added. The mixture was refluxed and stirred at 120°C for 24 hours under nitrogen protection. After the reaction, the solid product was centrifuged to obtain the solid product. The solid product was repeatedly washed with acetone and dichloromethane for 3 times, and vacuum dried at 40°C for 12 hours to obtain aminopropyl-functionalized nano-silica.

[0131] S2. Preparation of carboxyl functionalized nano-silica:

[0132] Weigh 2 g of the aminopropyl functionalized nano-silica prepared above, disperse it in 50 mL of xylene, add 0.2 g of maleic anhydride, reflux and stir at 140°C under nitrogen protection for 6 hours, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain carboxyl functionalized nano-silica.

[0133] S3. Preparation of modified nano-silica:

[0134] Weigh 2 g of the prepared carboxyl functionalized nano-silica, disperse it in 50 mL of toluene, add 0.15 g of dicyclohexylcarbodiimide (DCC) and 0.03 g of 4-dimethylaminopyridine (DMAP), activate it at room temperature with stirring for 0.5 hour, then add 0.6 g of tetraethylenepentamine (p is 3), continue to react at room temperature for 12 hours, wash it repeatedly with methanol for 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain modified nano-silica A2 with the structure of formula (1), wherein n is 0, m is 3, and x is 3.

[0135] The particle size of the modified nano-silicon dioxide A2 is 200 nm and the specific surface area is 100 m 2 / g, and the amino content is 0.2mmol / g.

[0136] like Figure 4 As shown, the prepared modified nano-silica A2 is dispersed more evenly in water and has good dispersibility; Figure 5 and Figure 6 They are transmission electron microscope TEM and scanning electron microscope SEM images of high-density amino-modified nano-silica. Figure 5-6 It can be seen that the high-density amino-modified nano-silica particles are relatively uniform. The modified nano-silica A2 was tested using a laser particle size analyzer, and its dispersion coefficient PDI was 0.13.

[0137] Example 3

[0138] The method is consistent with that of Preparation Example 1, except that the specific surface area of ​​the nano-silicon dioxide particles M is 100 m 2 / g, and in step S3, the amount of polyethyleneimine (molecular weight 1500) is 0.4g;

[0139] The particle size of the modified nano-silicon dioxide A3 is 30 nm, and the specific surface area is 230 m 2 / g, and the amino content is 0.1mmol / g.

[0140] The final dispersion coefficient PDI of A3 was 0.13.

[0141] Example 4

[0142] The method is consistent with that of Preparation Example 1, except that in step S3, the amount of polyethyleneimine used is 0.04 g;

[0143] The modified nano-silicon dioxide A4 has a particle size of 30 nm and a specific surface area of ​​300 m 2 / g, and the amino content is 0.05mmol / g.

[0144] The final dispersion coefficient PDI of A4 was 0.12.

[0145] Example 5

[0146] The method is consistent with that of Preparation Example 1, except that in step S1, aminopropyltriethoxysilane is replaced by aminopropyltrimethoxysilane;

[0147] The modified nano-silicon dioxide A5 has a particle size of 30 nm and a specific surface area of ​​300 m 2 / g, and the amino content is 2mmol / g.

[0148] The final test dispersion coefficient PDI of A5 is 0.14.

[0149] Example 6

[0150] The method is consistent with that of Preparation Example 1, except that in step S1, the average particle size of the nano-silicon dioxide is 800 nm and the specific surface area is 5 m 2 / g;

[0151] The particle size of the modified nano-silica A6 prepared was 800 nm and the specific surface area was 50 m 2 / g, and the amino content is 0.02mmol / g.

[0152] The final test dispersion coefficient PDI of A6 is 0.13.

[0153] Example 7

[0154] The method is consistent with that of Preparation Example 1, except that in step S3, the amount of polyethyleneimine (molecular weight 3000) used is 0.01 g;

[0155] The modified nano-silicon dioxide A7 has a particle size of 30 nm and a specific surface area of ​​400 m 2 / g, and the amino content is 0.01mmol / g.

[0156] The final test dispersion coefficient PDI of A7 is 0.13.

[0157] Example 8

[0158] The method is consistent with that of Preparation Example 1, except that in step S2, the amount of maleic anhydride used is 0.02 g;

[0159] The particle size of the modified nano-silica A8 obtained was 30 mm and the specific surface area was 250 m 2 / g, and the amino content is 0.015mmol / g.

[0160] The final test dispersion coefficient PDI of A8 is 0.14.

[0161] Example 9

[0162] The method is consistent with that of Preparation Example 1, except that in step S1, the amount of aminopropyltriethoxysilane used is 0.033 g;

[0163] The particle size of the modified nano-silica A9 obtained was 30 nm and the specific surface area was 280 m 2 / g, and the amino content is 0.4mmol / g.

[0164] The final test dispersion coefficient PDI of A9 is 0.14.

[0165] Example 10

[0166] The method is consistent with that of Preparation Example 1, except that in step S1, aminopropyltriethoxysilane is replaced by aminopropylmethyldiethoxysilane;

[0167] The particle size of the modified nano-silica A9 obtained was 30 nm and the specific surface area was 280 m 2 / g, the amino content is 0.4mmol / g. Wherein n is 1, m is 2, and x is 3.

[0168] The final test dispersion coefficient PDI of A9 is 0.13.

[0169] Comparative Example 1

[0170] S1. Weigh 1g of dimethylphenylsilane and disperse it in 50mL of xylene. Add 0.098g of maleic anhydride. Reflux and stir at 160°C for 6 hours under nitrogen protection. After the reaction, wash it repeatedly with methanol for 3 times. Vacuum dry it at 40°C for 12 hours to obtain carboxyl functionalized silicone.

[0171] S2, weigh 2g of the above carboxyl functionalized silicone and disperse it in 50mL toluene, add 0.051g of diisopropylcarbodiimide (DIC) and 0.122g of 1,8-diazabicycloundec-7-ene (DBU), stir and activate at room temperature (25°C) for 1 hour, then add 0.45g of polyethyleneimine (molecular weight of 1500), continue to react at room temperature for 12 hours, after the reaction is completed, wash it repeatedly with methanol for 3 times, and vacuum dry it at 40°C for 12 hours to obtain modified silicone D1;

[0172] The modified silicone D2 has a particle size of 30 nm and a specific surface area of ​​300 m 2 / g, and the amino content is 2mmol / g.

[0173] The final dispersion index (PDI) of D1 was 0.45.

[0174] Comparative Example 2

[0175] The method is consistent with that of Preparation Example 1, except that the polyamino modification of step S3 is not performed, and finally carboxyl functionalized nano-silica D2 is obtained;

[0176] The particle size of the carboxyl functionalized nano-silicon dioxide D2 is 30 nm and the specific surface area is 100 m 2 / g, and the amino content is 0mmol / g.

[0177] The final dispersion coefficient PDI of D2 was 0.13.

[0178] Test Case

[0179] The modified nano-silicon dioxide obtained in the examples and comparative examples was used as a curing agent and applied to epoxy resin to test its curing performance on epoxy resin. The epoxy resin used in the experiment was brand E51, purchased from Baling Petrochemical.

[0180] Specifically, 100g of epoxy resin and 30g of materials prepared by A1-A10 and D1-D2 were mixed and cured at a curing temperature of 130°C for 2 hours to obtain cured epoxy resins E1-E10 and DE1-DE2. The compressive strength and glass transition temperature of the cured epoxy resins E1-E10 and DE1-DE2 were tested.

[0181] Among them, the compressive strength is tested by 5969 high and low temperature universal material testing machine;

[0182] The glass transition temperature was measured by DSC method.

[0183] The test results are shown in the table below:

[0184] Table 1

[0185]

[0186]

[0187] It can be seen from the above results that the modified nano-silica provided by the present invention is used as a curing agent for epoxy resin, and the prepared cured epoxy resins E1-E10 have good effects, with a compressive strength of not less than 28 MPa and a glass transition temperature of not less than 120°C.

[0188] The preferred embodiments 1-2 and 5 are further satisfied, and the cured epoxy resins E1-E2 and E5 prepared therefrom obtain better technical effects. Specifically, the compressive strength is not less than 48 MPa, and the glass transition temperature is not less than 135°C.

[0189] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified nano-silicon dioxide, characterized in that: The modified nano-silicon dioxide has a structure shown in formula (1): Wherein, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms; n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3; A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.

2. The modified nano silicon dioxide according to claim 1, wherein The acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride; Preferably, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000 having a structure shown in formula (2): Here, p is an integer from 1 to 6.

3. The modified nano silicon dioxide according to claim 1 or 2, wherein The particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g; Preferably, the particle size of the modified nano-silicon dioxide is 10-500nm and the specific surface area is 50-500m 2 / g; Preferably, the amino content of the modified nano-silica is 0.1-5 mmol / g.

4. A method for preparing modified nano-silicon dioxide, characterized in that: The method comprises the following steps: S1. In the presence of a protective gas, dispersing nano-silica particles M in a first solvent, adding aminosilane to carry out a first reaction, and obtaining amino-functionalized nano-silica as shown in formula (3); S2, in the presence of a second solvent, subjecting the amino-functionalized nano-silica to a second reaction with an acid anhydride compound to obtain a carboxyl-functionalized nano-silica represented by formula (4); S3. In the presence of an alkaline catalyst, the carboxyl-functionalized nano-silica is mixed with a condensation agent, activated, and then a polyamino compound is added to carry out a third reaction to obtain modified nano-silica.

5. The method according to claim 4, wherein: In step S1, the mass ratio of the nano-silica particles M to the aminosilane is 5-100:1; Preferably, the aminosilane is selected from at least one of aminopropyltriethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane and aminopropylmethyldiethoxysilane; Preferably, the conditions of the first reaction include: reaction temperature of 120-160°C, reaction time of 2-24h; Preferably, in step S2, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 5-100:1; Preferably, the conditions of the second reaction include: reaction temperature of 90-160°C, reaction time of 2-12h; Preferably, the first solvent and the second solvent are each independently selected from at least one of toluene, xylene, benzene and N,N-dimethylformamide.

6. The method according to claim 4 or 5, wherein: In step S3, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1: 0.05-0.5: 0.01-0.1: 0.1-5; Preferably, the condensing agent is selected from one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide; Preferably, the base catalyst is selected from at least one of 4-dimethylaminopyridine, 1,8-diazabicycloundec-7-ene and triethylamine; Preferably, the conditions of the third reaction include: reaction temperature of 0-40°C, reaction time of 2-48h; Preferably, the activation conditions include: an activation temperature of 10-25° C. and an activation time of 8-24 h.

7. The modified nano silicon dioxide prepared by the method described in any one of claims 4 to 6.

8. Use of the modified nano-silicon dioxide described in claims 1-3 and 7 as a curing agent in epoxy resin.

9. An epoxy resin composition, characterized in that The epoxy resin composition comprises a curing agent component and a resin component; The curing agent component contains the modified nano-silicon dioxide described in claim 1-3 or 7; The resin component includes epoxy resin. Wherein, the curing agent component and the resin component exist independently of each other.

10. A cured epoxy resin, characterized in that: The cured epoxy resin is prepared from the epoxy resin composition according to claim 9.

Citation Information

Patent Citations

  • Preparation method and application of modified nano-silicon dioxide toughened epoxy resin

    CN103113712A

  • Preparation of epoxy-terminated hyperbranched polyester modified nano silica organic-inorganic hybrid material

    CN106565963A

  • Dicarboxylic anhydride dispersion sol of silane-treated modified metal oxide, method for producing the same, epoxy curing agent containing the same, and epoxy resin cured product

    JP2013028481A

  • An organic / inorganic nanohybrid and preparation methodthereof using an aminosilane precusor

    KR1020040059346A